2021
DOI: 10.3390/molecules26113144
|View full text |Cite
|
Sign up to set email alerts
|

C-11, a New Antiepileptic Drug Candidate: Evaluation of the Physicochemical Properties and Impact on the Protective Action of Selected Antiepileptic Drugs in the Mouse Maximal Electroshock-Induced Seizure Model

Abstract: C-11 is a hybrid compound derived from 2-(2,5-dioxopyrrolidin-1-yl) propanamide, with a wide spectrum of anticonvulsant activity and low neurotoxicity. The aim of this study was to determine the effects of C-11 on the protective action of various antiepileptic drugs (i.e., carbamazepine CBZ, lacosamide LCM, lamotrigine LTG, and valproate VPA) against maximal electroshock-induced seizures (MES) in mice, as well as its neuroprotective and physicochemical/pharmacokinetic properties. Results indicate that C-11 (30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…compounds at various pretreatment times (i.e., 15, 30, 60, 120 min) ranged from 1.7 to even 6.2 ( Table 3 ). Taking into account the fact that, according to the literature data, compounds with a protective index value above 5, and sometimes even 2, should be taken for further research, and if we take into account the PI values obtained by valproate, the most commonly used in pharmacotherapy of epilepsy, then it can be concluded that the compounds constitute a group of good candidates for further research [ 30 , 31 ]. The anticonvulsant effect of 3 and 4 , expressed as ED 50 values at their peaks of anticonvulsant activity, was also higher than that of valproate—the most commonly used AED ( p < 0.0001, Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…compounds at various pretreatment times (i.e., 15, 30, 60, 120 min) ranged from 1.7 to even 6.2 ( Table 3 ). Taking into account the fact that, according to the literature data, compounds with a protective index value above 5, and sometimes even 2, should be taken for further research, and if we take into account the PI values obtained by valproate, the most commonly used in pharmacotherapy of epilepsy, then it can be concluded that the compounds constitute a group of good candidates for further research [ 30 , 31 ]. The anticonvulsant effect of 3 and 4 , expressed as ED 50 values at their peaks of anticonvulsant activity, was also higher than that of valproate—the most commonly used AED ( p < 0.0001, Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, KA-11 significantly stimulated the proliferation migration and differentiation of newborn cells into neurons and astrocytes, as well as protected the cognitive functions in the mouse PILO-induced status epilepticus (PILO-induced SE) [11]. Finally, our last studies using KA-11 in combination with several selected ASDs in the mouse model of an MES test indicated a significant pharmacodynamic impact of KA-11 on the antiseizure action of two ASDs, lacosamide and valproate, with no adverse effects among the tested drugs [8]. Moreover, in silico studies indicated that KA-11 meets the drug-likeness criteria resulting from Lipinski's [12] and Veber's [13] rules, as well as the prediction of gastrointestinal absorption and brain penetration (according to Instant JChem by the ChemAxon software version 21.4.0).…”
Section: Introductionmentioning
confidence: 82%
“…Over the past several years, we have been conducting intensive research on a new hybrid compound, a 2-(2,5-dioxopyrrolidin-1-yl)propanamide derivative, compound KA-11 (also named C-11), which, as a hybrid molecule, combines structural fragments of three ASDs: ethosuximide, levetiracetam and 2 of 23 lacosamide. The results of our previous in vitro studies and animal models of epilepsy clearly showed that the hybrid KA-11 has strong antiseizure and neuroprotective properties in acute mouse seizure models: maximal electroshock seizures (MES), subcutaneous pentylenetetrazole (scPTZ) seizures, pilocarpine (PILO) seizures and the 6 Hz seizure model [6,8]. Moreover, we have shown that KA-11 suppresses seizures after repeated administration of PTZ in the mouse kindling model of epilepsy [9].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similar to AS-1, the same research team developed a series of multifunctional ASMs with hybrid structures integrating fragments of ethosuximide, levetiracetam, and lacosamide [69][70][71]. C-11 (former name KA-11) is recognized as a new hybrid compound derived from 2-(2,5-dioxopyrrolidin-1-yl) propanamide [72]. As shown in previous quantitative studies, C-11 demonstrated promising, broad-spectrum antiseizure activities in several preclinical animal models including MES, s.c. PTZ, and 6 Hz (32 mA) psychomotor seizure models [73].…”
Section: -(25-dioxopyrrolidin-1-yl) Propanamide Derivative (C-11)mentioning
confidence: 99%